Factors affecting solvability analysis of Indonesian sharia life insurance companies - Puspitasari, Novi; Hidayat, Sutan Emir; Nurhayati, Nurhayati; Hasanah, Shofiatul (Universitas Negeri Surabaya, 2023)
Examining and analyzing the impact of premiums, claims, investment returns, reinsurance, and underwriting on the solvency of Islamic life insurance firms in Indonesia is the goal of this study, with firm size as the control variable. In this study, the entire population serves as the total sample. The sampling method is saturation sampling of 15 companies, and the research range is from 2016 to 2020, with a total of 75 observations. The analytical method uses multiple linear regression analyses: premiums, investment returns, and underwriting impact solvency and support resource-based theory. However, regarding the impact of Claims, Reinsurance, and control variables, namely, The level of solvency is not significantly impacted by the size of the company; it is contrary to Resource Based Theory. This is rationally found in the Islamic insurance business model, which is different from the conventional insurance business model so that the solvency of Islamic insurance is not affected by claims, reinsurance, and company size.